THE INFLUENCE OF THE MARKETING SYSTEM AND THE USE OF E-COMMERCE ON THE SALE OF WRITTEN AND STAMPED BATIK PRODUCTS IN BATIK PUSAKA BANTEN - Faisal, Ade; Dadan Hawari, Achmad (DESANTA (Indonesian of Interdisciplinary Journal), 2025)
This research aims to analyze the influence of the marketing system and the use of E-commerce on product sales at Batik Pusaka Banten, a producer of written and stamped batik. Facing economic changes, Batik Pusaka Banten needs to adopt relevant marketing strategies to increase product visibility and expand consumer reach. Using quantitative methods with purposive sampling techniques, this research found that both the marketing system and E-commerce had a significant effect on sales, both partially and simultaneously. The results of the analysis show that the marketing system has a t value of 3.040 and E-commerce reaches a t value of 7.034. Simultaneously, the two variables show a significant influence on sales with a calculated F value of 84.505. The R-Square value of 0.687 indicates that the marketing and E-commerce system explains 68.7% of sales variations, while the remaining 31.3% is influenced by other factors such as economic conditions, market trends and consumer behavior.